Intraspecific Variability and Phenetic Relationships of Centella Asiatica (L.) Urb. Accessions from Central Java Based on Morphological Characters’ - Maruzy, Anshary; Susandarini, Ratna (Journal of Tropical Biodiversity and Biotechnology, 2024)
Centella asiatica (L.) Urb. is a plant species native to Java and one of the main basic materials in traditional and modern medicine. This study is the first to report the intraspecific variation and taxonomic relationships of C. asiatica accession from natural populations in Central Java.  The purpose of this study was to reveal phenotypic variations of C. asiatica populations and to asses phenetic relationships based on morphological characters. Thirty-two accessions of C. asiatica were collected from natural populations from eight mountains in Central Java. Observation on vegetative organs resulted in 25 morphological characters as a basis for assessing phenetic relationships using cluster analysis and principal component analysis. Result of cluster analysis showed that the grouping of accessions was not correlated to the localities from where the samples were collected, although there was a tendency that accessions from the same localities grouped in one cluster. The results of this study confirmed the existence of intraspecies morphological variability in C. asiatica which was not affected by geographical aspects. Results of principal component analysis indicated that the grouping of accessions was mainly determined by similarities in petiole color, stolon color, leaf margin, petiole length, stolon length, and leaf color. Given that the characters contributing to the grouping of accessions were mainly qualitative characters, the results indicated a genetic basis underlying phenotypic variations of C. asiatica accession.